The Effect of Land Scarcity on Capital Distribution Under Mortgage Law in Indonesia - Chandra Yusuf (International Conference On Law And Social Sciences, 2024)
The company as a Bank Debtor requires capital to develop its business. Land as a production factor in industry is also used as collateral in the Credit Agreement. The debtor will pledge the land fixed assets based on Law Number: 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land (Mortgage Rights Law). The Bank and the Debtor will make a Deed of Granting Mortgage Rights (APHT). When the debtor is unable to repay the loan, the bank can sell the debtor's collateral to recover it. The sale of the collateral can be done through an auction so that the Debtor gets a market price. This auction is intended to repay the Debtor's remaining loan. The Mortgage Law as a legal coding legalizes the transfer of rights to the debtor's land to the third-party winner of the auction. The problem is that land is a rare good that is increasing in value. Control of land rights has limitations in its concrete physical form. Demand for land as collateral is scarce. Companies that need capital will be constrained by having to own land as collateral. This will lead to injustice in owning capital in society. A company that already has large capital and owns land at a high price can borrow funds from the bank. The researcher uses a normative approach to legal regulations and analyzes from the angle of economic analysis that can explain the scarcity of land. Land scarcity makes land prices soar. Land encoding through the Mortgage Law.